2017
DOI: 10.1159/000477719
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Effectiveness of Ultrasound-Guided Corticosteroid Injection with and without Needle Release of the Transverse Carpal Ligament in Carpal Tunnel Syndrome

Abstract: Background: To compare the clinical effectiveness of ultrasound-guided corticosteroid injection with and without needle release of the transverse carpal ligament (TCL) in carpal tunnel syndrome (CTS). Methods: Between May 2014 and June 2016, 52 patients (56 wrists) with CTS were included in this study. Among these patients, 28 wrists were treated with ultrasound-guided corticosteroid injection plus needle release of the TCL (group A) and 28 wrists were treated with a single ultrasound-guided corticosteroids in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Other studies aimed to analyze the effects of conservative treatments, such as taping, splint, or ultrasounds, did not demonstrate significant improvements in CSA of the median nerve [ 42 , 49 ]. Previous studies reported improvements after a surgical intervention or corticosteroid infiltration on CSA assessment [ 54 , 55 ]. It is important to consider the possible adverse effects derived from these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies aimed to analyze the effects of conservative treatments, such as taping, splint, or ultrasounds, did not demonstrate significant improvements in CSA of the median nerve [ 42 , 49 ]. Previous studies reported improvements after a surgical intervention or corticosteroid infiltration on CSA assessment [ 54 , 55 ]. It is important to consider the possible adverse effects derived from these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…No SR comparing PUSG techniques of CTR with any other intervention were found. Only 5of the 30 studies reviewed here describing 4 different techniques were RCT [11][12][13][14][15]; a further 3 studies were NoRCT [10,16,17]; and 22 were NoC .…”
Section: Types Of Studymentioning
confidence: 99%
“…Three studies by two groups [15][16][17] undertook steroid injection in the same surgical act as FR section. Section direction: anterograde Incision direction: not applicable Entry point: palmar, 5 mm distal to the SAPA, distal edge of the TCL division determined sonographically in the "duck's beak" described by Rojo Manaute et al (38)a previously reported sonographic zone was defined as the space between the median nerve and the closest ulnar vascular structure.…”
Section: Interventionsmentioning
confidence: 99%
“…34 Mechanical hydrodissection may relieve these adhesions 46 and is far easier to perform using an in-plane transverse approach. In addition to the injection, operators can repeatedly fenestrate or "release" the transverse carpal ligament with a needle, 17,47 or perform a minimally invasive release with a specialized surgical instrument. 18,19,48 Ulnar Neuropathy at the Elbow (Cubital Tunnel Syndrome).…”
Section: Fibular (Peroneal) Nerve At the Fibular Neck Neuropathymentioning
confidence: 99%